The clinical potential of PDL-1 pathway and some related micro-RNAs as promising diagnostic markers for breast cancer - Eman A. Al-Sharabass; Motawa E. EL-Houseini; Heba Effat; Sherif Abdelaziz Ibrahim; Mona S. Abdellateif (Molecular Medicine)
Abstract Background Immune checkpoint pathways play important roles in breast cancer (BC) pathogenesis and therapy. Methods Expression levels of programmed cell death protein 1 (PD-1), cytotoxic T-lymphocyte–associated antigen 4 (CTLA-4), programmed death-ligand 1 (PD-L1), Forkhead box P3 (FOXP3), miR-155, and miR-195 were assessed in the peripheral blood of 90 BC patients compared to 30 healthy controls using quantitative real-time PCR (qRt-PCR). The plasma level of soluble MHC class I chain related-protein B (MIC-B) protein was assessed using the enzyme linked immunosorbent assay (ELISA) technique. The data were correlated to the clinico-pathological characteristics of the patients. Results There was a significant increase in the expression levels of PDL-1 [17.59 (3.24–123), p < 0.001], CTLA-4 [23.34 (1.3–1267), p = 0.006], PD-1 [10.25 (1–280), p < 0.001], FOXP3 [11.5 (1–234.8), p = 0.001], miR-155 [87.3 (1.5–910), p < 0.001] in BC patients compared to normal controls. The miR-195 was significantly downregulated in BC patients [0.23 (0–0.98, p < 0.001]. The plasma level of MIC-B was significantly increased in the BC patients [0.941 (0.204–6.38) ng/ml], compared to the control group [0.351 (0.211–0.884) ng/mL, p < 0.00]. PDL-1, CTLA-4, PD-1, and FOXP3 achieved a specificity of 100% for distinguishing BC patients, at a sensitivity of 93.3%, 82.2%, 62.2%, and 71.1% respectively. The combined expression of PDL-1 and CTLA-4 scored a 100% sensitivity and 100% specificity for diagnosing BC (p < 0.001). The sensitivity, specificity, and AUC of miR-155 were 88.9%, 96.7%, and 0.934; respectively (p < 0.001). While those of miR-195 were 73.3%, 60%, and 0.716; respectively (p = 0.001). MIC-B expression showed a 77.8% sensitivity, 80% specificity, and 0.811 AUC at a cutoff of 1.17 ng/ml (p < 0.001). Combined expression of miR-155 and miR-195 achieved a sensitivity of 91.1%, a specificity of 96.7%, and AUC of 0.926 (p < 0.001). Multivariate analysis showed that PDL-1 (OR:13.825, p = 0.004), CTLA-4 (OR: 20.958, p = 0.010), PD-1(OR:10.550, p = 0.044), MIC-B (OR: 17.89, p = 0.003), miR-155 (OR: 211.356, P < 0.001), and miR-195(OR:0.006, P < 0.001) were considered as independent risk factors for BC. Conclusions The PB levels of PDL-1, CTLA-4, PD-1, FOXP3, MIC-B, miR-155, and miR-195 could be used as promising diagnostic markers for BC patients.